Influencer Wisdom As A Conceptual Model To Understand Influencer Strategies, Tactics, And Success - Asaad, Mariam Ashraf (AUC Knowledge Fountain, 2026)
The global influencer marketing industry, valued at over $16 billion, lacks frameworks for understanding responsible and sustainable influence practices. While current research focuses on metrics-driven success measures, this study addresses the gap between commercial achievement and ethical influence by developing a comprehensive Influencer Wisdom Framework. Drawing from wisdom theory, consumer behavior research, and social cognitive theory, this research extends the concept of wisdom to digital influence contexts through qualitative investigation of successful influencer practices. Twenty in-depth interviews with diverse influencers across multiple platforms and niches were analyzed using systematic thematic analysis. The study identifies five interconnected dimensions of influencer wisdom: Intentionality and Authenticity (deliberate commitment to genuine self-expression), Ethical Contemplation (systematic consideration of moral implications in partnerships and content), Purpose-Driven Impact (creating meaningful value beyond personal gain), Emotional Mastery (sophisticated management of psychological challenges), and Growth Mindset and Openness (commitment to continuous learning and adaptation). The framework reveals that sustainable influencer success requires balancing measurable outcomes with unmeasurable wisdom factors, challenging industry emphasis on quantitative metrics alone. Findings demonstrate how wisdom-based practices create deeper audience connections, more resilient careers, and positive social impact. This research contributes to influencer marketing theory by providing the first comprehensive framework for responsible influence practices, offering practical guidance for creators, brands, platforms, and educators while establishing foundations for future research in digital career development and ethical technology use.